Stimuli Responsive Nitric Oxide-Based Nanomedicine for Synergistic Therapy - Yijun Zhao (MDPI AG, 2021)
Gas therapy has received widespread attention from the medical community as an emerging and promising therapeutic approach to cancer treatment. Among all gas molecules, nitric oxide (NO) was the first one to be applied in the biomedical field for its intriguing properties and unique anti-tumor mechanisms which have become a research hotspot in recent years. Despite the great progress of NO in cancer therapy, the non-specific distribution of NO in vivo and its side effects on normal tissue at high concentrations have impaired its clinical application. Therefore, it is important to develop facile NO-based nanomedicines to achieve the on-demand release of NO in tumor tissue while avoiding the leakage of NO in normal tissue, which could enhance therapeutic efficacy and reduce side effects at the same time. In recent years, numerous studies have reported the design and development of NO-based nanomedicines which were triggered by exogenous stimulus (light, ultrasound, X-ray) or tumor endogenous signals (glutathione, weak acid, glucose). In this review, we summarized the design principles and release behaviors of NO-based nanomedicines upon various stimuli and their applications in synergistic cancer therapy. We also discuss the anti-tumor mechanisms of NO-based nanomedicines in vivo for enhanced cancer therapy. Moreover, we discuss the existing challenges and further perspectives in this field in the aim of furthering its development.